Pengaruh Media Sosial Instagram, Word Of Mouth, Dan Preferensi Wisatawan Terhadap Keputusan Berkunjung Wisatawan Di Wisata Air Balekambang Gondang Mojokerto - Azna, Nurul Izza Aulia; Basalamah, Muhammad Ridwan; Rahmawati, Rahmawati (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study was to determine and analyze the effect of social media instagram, word of mouth, and tourist preferences on tourist visiting decisions on water tourism balekambang gondang mojokerto case study on tourists of water tourism balekambang gondang mojokerto. This study uses a quantitative approach with sample determination using the Maholtra formula due to an unknown population. From the results of the calculation, a sample of 95 was obtained. Likert scale is used as a measurement tool. Primary data is collected through a questionnaire distributed via google form. Data testing through validity test, reliability test, classical assumption test, multiple linear regression test, hypothesis testing, and coefficient of determination test using the help of SPSS 26. The results of this study indicate that Instagram social media, word of mouth, and tourist preferences simultaneously affect tourist visiting decisions and individually Instagram social media, word of mouth, and tourist preferences have a significant effect on tourist visiting decisions. Keywords: Instagram Social Media, Word Of Mouth, Tourist Preferences, Tourist Visiting Decisions